Dry needling for orofacial pain: a systematic review and meta-analysis of randomized clinical trials - Adrian Kuzdzal; Edzard Ernst; Pawel Posadzki; Zbigniew Wronski (PAIN Reports)
Abstract. Orofacial pain (OFP) is an ache in the front part of the head and typically has musculoskeletal, dental, neural, or sinogenic origin. Dry needling (DN) is the insertion of a solid sterile fine needle through the skin aimed at deactivating the myofascial trigger points has extensively been studied in randomized clinical trials (RCTs). This systematic review was aimed at evaluating the evidence base for the effectiveness of DN for OFP. We searched Medline, Cochrane Central, and Web of Science (from their respective inceptions to February 2024) for RCTs evaluating the effectiveness of DN in patients with OFP. Studies with individuals suffering from cervicogenic or tension type headaches as well as observational studies were excluded. Primary outcomes were pain intensity and severity; secondary outcomes were disability, quality of life, and adverse effects. The review adhered to the methods described by in the Cochrane Handbook. Twenty-four RCTs with a total of 1,318 patients suffering from OFP were included. Most had an unclear or high risk of bias, and the quality of the evidence ranged from very low to low for all comparisons and outcomes. A meta-analysis suggested that, compared with usual care alone, DN + usual care had no effect on pain intensity (visual analogue scale) (standardized mean difference = −1.89, 95% confidence intervals −5.81 to 2.02, very low certainty evidence) at follow-ups of up to 6 weeks. There is little reliable evidence for the effectiveness of DN in reducing OFP. Future, larger, more rigorous studies might reduce the existing uncertainties.